Retraction Note: Neonatal congenital mesoblastic nephroma that caused respiratory oncologic emergency early after birth: a case report - Hirotaka Kato; Yasuyuki Mitani; Taro Goda; Hiroki Yamaue (BMC, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12887-022-03210-8.